Studying haloanisoles interaction with olfactory receptors - Teixeira, Carla S. Silva (2017)
In this paper, computational means were used to explain and predict the interaction of several odorant molecules, including three haloanisoles, 2,4,6-trichloroanisole (TCA), 2,4,6-tribromoanisole (TBA), and 2,4,6-trichlorophenol (TCP), with three olfactory receptors (ORs): OR1A1, OR1A2, and OR3A1. As the X-ray structure of these ORs is not known, the three-dimensional structure of each OR was modeled by homology modeling. The structures of these ORs were stabilized by molecular dynamic simulations and the complexes of the odorant molecules with each ORs were generated by molecular docking. The theoretical results have shown that each OR has distinct but well-defined binding regions for each type of odorant molecules (aldehydes and alcohols). In OR3A1, the aldehydes bind in the bottom region of the binding pocket nearby Ser257 and Thr249. In the paralogues OR1A1 and OR1A2, the aldehydes tend to interact in the top region of the binding pocket and close to a positively charged lysine. On the other hand, the alcohols interact in the bottom region of the active site and close to a negatively charged aspartate. These results indicate that when aldehydes and alcohols odorants compete in these two ORs, the aldehydes can block the access of the alcohols odorants to their specific binding site. This observation goes in line with the experimental data that reveals that when the odorant is an aldehyde, a lower quantity of ligand is needed to cause 50% of the maximum response (lower EC50), when compared with the alcohols. The theoretical results have also allowed to explain the differences in the activity of (S)-(−)-citronellol in the wild-type and mutated OR1A1. The theoretical results show that Asn109 has a preponderant role in this matter, since when it is mutated, it leads to a conformational rearrangement of the binding pocket that prevents the interaction of (S)-(−)-citronellol with Asp111 that was shown to be important for the OR activation. The good agreement between the theoretical and experimental results also lead us to study the potential interaction of the haloanisoles, TCA, TBA, and TCP with these ORs. The results have shown that these compounds can compete with other known agonists/antagonists for the access to the binding regions of ORs. These results may partially explain the capability of these compounds to give a musty odor to food and beverages at very low concentrations.